1995
DOI: 10.1111/j.1749-6632.1995.tb32452.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Imidazolines on Catecholamine Release in Pithed Spontaneously Hypertensive Rats

Abstract: The actions of the imidazoline derivatives clonidine, moxonidine, and rilmenidine and of the recently discovered clonidine-displacing substance agmatine on stimulation-induced norepinephrine overflow and epinephrine release were studied in pithed spontaneously hypertensive rats. All three imidazolines dose-dependently decreased norepinephrine overflow and led to an increase in epinephrine release when the highest dose of each compound was injected. The alpha 2-adrenoceptor antagonist rauwolscine shifted the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…For this reason we studied the effects of agmatine: (1) by injecting agmatine intravenously or directly into the central nervous system of pithed or anaesthetized spontaneously hypertensive rats (SHR); (2) by determining the cardiovascular interaction between agmatine and clonidine; and (3) by identifying a mechanism which might be responsible for the agmatine‐induced regulation of blood pressure and heart rate. The use of SHR in our study was based on experience gained with this model from earlier studies; clonidine and agmatine were both shown to influence blood pressure and/or catecholamine overflow in pithed SHR (Häuser & Dominiak, 1995; Häuser et al ., 1995). Furthermore, CDS was shown to be increased in plasma of hypertensive patients and was positively correlated with blood pressure (Dontenwill et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason we studied the effects of agmatine: (1) by injecting agmatine intravenously or directly into the central nervous system of pithed or anaesthetized spontaneously hypertensive rats (SHR); (2) by determining the cardiovascular interaction between agmatine and clonidine; and (3) by identifying a mechanism which might be responsible for the agmatine‐induced regulation of blood pressure and heart rate. The use of SHR in our study was based on experience gained with this model from earlier studies; clonidine and agmatine were both shown to influence blood pressure and/or catecholamine overflow in pithed SHR (Häuser & Dominiak, 1995; Häuser et al ., 1995). Furthermore, CDS was shown to be increased in plasma of hypertensive patients and was positively correlated with blood pressure (Dontenwill et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in conscious and pithed rabbits have supported the view that central sympathetic inhibition is mediated only via ␣ 2 -adrenoceptors (Urban et al, 1995;Bock et al, 1999;Szabo et al, 1999). In pithed, spontaneously hypertensive rats (SHR) and rabbits, rilmenidine and moxonidine decreased the stimulated overflow of noradrenaline (Hä user et al, 1995;Urban et al, 1995;Szabo et al, 1999). Because imidazoline derivatives were still able to reduce noradrenaline overflow dose dependently after rauwolscine pretreatment, an ␣ 2 -adrenoceptor-independent mechanism was suggested (Hä user et al, 1995).…”
mentioning
confidence: 81%
“…4) increased noradrenaline overflow dose dependently during ␣ 2 -adrenoceptor blockade, strengthening the idea of antagonism between efaroxan and moxonidine at I 1 -binding sites regarding noradrenaline release. Such a picture regarding noradrenaline release is paralleled when focusing on presynaptic ␣ 2 -adrenoceptors: a stimulation for example by the agonist moxonidine causes a decrease, whereas an inhibition by rauwolscine or phenoxybenzamine increases noradrenaline release (Hä user et al, 1995). However, our findings differ from in vitro findings in that the electrically evoked [ 3 H]noradrenaline overflow in the presence of phenoxybenzamine or rauwolscine was either diminished Molderings et al, 1997) or remained unchanged (Molderings and Göthert, 1998), a fact suggesting different modes/sites of action in in vivo and in vitro situations (see above for discussion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best way to demonstrate in vivo whether imidazoline binding sites would have some regulatory impact on noradrenaline release is to employ α 2A/C ‐double knockout (KO) mice. Since this animal model was not available to us, we decided to overcome the limitation of a competitive blockade of α 2 ‐adrenoceptors with rauwolscine (this α 2 ‐AR antagonist was used in previous studies3) by performing experiments in pithed rats under irreversible α 2 ‐AR blockade (by using phenoxybenzamine) or blockade of I 1 ‐receptors (by using AGN192403). Thus, the aim of this study was to determine whether imidazoline binding sites contribute to the moxonidine‐induced modification of noradrenaline release in vivo, and if so, to specify the subtype of imidazoline binding sites involved in mediating this effect.…”
Section: Introductionmentioning
confidence: 99%